Strengthening Banuroja Multicultural Social Integration from Social Conflict Threats Socio-Cultural Ethnographic Study in Gorontalo - Wahyudin Noe; Epin Saepudin; Irwan Efendy; Irwan Djumat (Department of Civic Education, 2022)
This research was motivated by the researcher’s anxiety about the nation’s problems that seem to never end from social conflicts related to ethnicity and religion, because of the attitude of sectoral egoism and intolerance towards diversity. The people of Banuroja are very aware of the impact of risks if social conflict befalls their citizens. This can happen due to a lack of understanding in accepting diversity as a necessity. Their critical readiness has been built very strongly, where seeing diversity is not a threat to people's lives. Therefore, it is important to strengthen social integration in multicultural societies as practiced by the Banuroja community. This study aims to describe the efforts of the Banuroja multicultural community in strengthening social integration in order to avoid the threat of conflict in their communities. This research used a qualitative approach with ethnographic study methods. The results showed that strengthening social integration in the multicultural society of Banuroja was carried out through (1) Strengthening tolerance in the midst of community diversity; 2) Prevent the emergence of sectoral egoism and foster an attitude of solidarity; and 3) Strengthening the role of community leaders as unifier from the threat of social conflict.